2014
DOI: 10.1182/blood-2013-07-516948
|View full text |Cite
|
Sign up to set email alerts
|

The F-BAR protein PSTPIP1 controls extracellular matrix degradation and filopodia formation in macrophages

Abstract: Key Points• PSTPIP1 regulates the transition from podosomes to filopodia in macrophages by modulating WASP activity.• The novel PSTPIP1-R405C mutant induces filopodia formation, increases matrix degradation, and is associated with severe pyoderma gangrenosum.PSTPIP1 is a cytoskeletal adaptor and F-BAR protein that has been implicated in autoinflammatory disease, most notably in the PAPA syndrome: pyogenic sterile arthritis, pyoderma gangrenosum, and acne. However, the mechanism by which PSTPIP1 regulates the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 63 publications
3
67
0
1
Order By: Relevance
“…26,32,33,53,[58][59][60] Even though the analysis of podosomes is a challenging task in 3D Matrigel, 26,31 we showed that HIV-1-infected and Nef-expressing (Figure 4A-B; data not shown), as defined for 3D podosomes. 26,31,61 The number of these protrusions per cell was increased on HIV-1 infection (8.6 vs 2.7, n .…”
Section: Hiv-1 Modifies Podosome Organization and Function Via Nefmentioning
confidence: 97%
“…26,32,33,53,[58][59][60] Even though the analysis of podosomes is a challenging task in 3D Matrigel, 26,31 we showed that HIV-1-infected and Nef-expressing (Figure 4A-B; data not shown), as defined for 3D podosomes. 26,31,61 The number of these protrusions per cell was increased on HIV-1 infection (8.6 vs 2.7, n .…”
Section: Hiv-1 Modifies Podosome Organization and Function Via Nefmentioning
confidence: 97%
“…An R405C amino acid exchange, for example, leads to reduced podosome formation, enhanced numbers of filopodia, and matrix degradation in human macrophages [61]. Interestingly, WASP is also involved in this phenomenon, as the R405C exchange results in impaired WASP binding of PSTPIP1 [61]. It has to be noted that, for both WAS and PAPA syndrome, the activity of WASP or PSTPIP1 is not restricted to podosomes or filopodia, but is likely to affect the whole cytoskeleton.…”
Section: Lost In Space? Podosome Formation In 3d Environmentsmentioning
confidence: 99%
“…Further important aspects include the discovery of podosome dynamics, comprising de novo formation, fusion, fission, and dissolution [38,40,57] and the identification of the podosome proteome, which is in the range of *200 proteins [58], comparable to that of focal adhesions [2] or invadopodia [59]. Moreover, macrophages enabled the discovery of podosomes in a 3D context [60], and also the link to potentially podosomebased diseases [5,61] (see paragraphs on podosomes in 3D environments and on podosome-associated diseases below).…”
Section: Introductionmentioning
confidence: 99%
“…Mice expressing a talin-1 mutant (W359A) that disrupts its binding to the NPxY motif in b 3 were protected from experimental thrombosis without undermining hemostasis by decelerating aIIbb3 activation. 1 I n addition to their essential role in hemostasis, platelets play a crucial role in a pathological thrombus formation, particularly within atherosclerotic arteries subjected to high shear stress. 2 As an initial step in thrombogenesis (or hemostasis), platelets adhere to altered vascular surfaces or exposed subendothelial matrices, then become activated and aggregate each other to grow thrombus (or platelet plug) volume.…”
Section: 10mentioning
confidence: 99%
“…4,5 In this issue of Blood, a novel mutation in the PSTPIP1 gene is described in a patient with PAPA syndrome. 1 The R405C mutation is the first mutation described in the SH3 domain of PSTPIP1. It is distant from the binding domain of PTP-PEST, which normally interacts with PSTPIP1.…”
mentioning
confidence: 99%